2015
DOI: 10.1371/journal.ppat.1004598
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Approaches Reveal a Key Role for DCs in CD4+ T Cell Activation and Parasite Clearance during the Acute Phase of Experimental Blood-Stage Malaria

Abstract: Dendritic cells (DCs) are phagocytes that are highly specialized for antigen presentation. Heterogeneous populations of macrophages and DCs form a phagocyte network inside the red pulp (RP) of the spleen, which is a major site for the control of blood-borne infections such as malaria. However, the dynamics of splenic DCs during Plasmodium infections are poorly understood, limiting our knowledge regarding their protective role in malaria. Here, we used in vivo experimental approaches that enabled us to deplete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 66 publications
5
35
0
Order By: Relevance
“…As these cells share various markers with inflammatory monocytes and conventional myeloid, as well as plasmocytoid DCs, some of the existing results in the literature may have missed that a significant proportion of DCs in this mouse malaria model are indeed MO-DCs. Previous studies using the P. chabaudi model identified inflammatory monocytes that express low levels of CD11c and a low frequency of CD11c + cells that were CD11b + F4/80 + (refs 19, 21). Here we provide evidences that in this model, splenic inflammatory monocytes and monocytes are progenitors of MO-DCs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As these cells share various markers with inflammatory monocytes and conventional myeloid, as well as plasmocytoid DCs, some of the existing results in the literature may have missed that a significant proportion of DCs in this mouse malaria model are indeed MO-DCs. Previous studies using the P. chabaudi model identified inflammatory monocytes that express low levels of CD11c and a low frequency of CD11c + cells that were CD11b + F4/80 + (refs 19, 21). Here we provide evidences that in this model, splenic inflammatory monocytes and monocytes are progenitors of MO-DCs.…”
Section: Discussionmentioning
confidence: 97%
“…This cytokine activates macrophages to produce toxic metabolites, such as reactive nitrogen intermediates and promotes Ig switch to the IgG2a/IgG2c, which mediate host resistance to Plasmodium infection in mice1150. In addition, both inflammatory monocytes and DCs can internalize and destroy infected RBCs in the spleens and mediate resistance to P. chabaudi infection in mice1921. However, depending on experimental setting, DCs may become refractory or impaired for presenting antigen to CD4 + T and CD8 + T cells5152.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As blood-stage malaria Ags are largely cell associated, the superiority of CD8 + DC in presenting MHC II-restricted malaria Ag shown in this study is likely a consequence of superiority in the capturing of malaria Ag. Indeed, a recent study has shown higher levels of P. chabaudi Ag uptake by CD8 + DC relative to CD4 + DC, when assessed at day 5 of infection (82).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the brain, the spleen is a focus in malaria research. Phagocytosis of iRBC by splenic DCs and the subsequent displacement and interaction of DCs with CD4 + ‐T cells was visualised by IVM, revealing a previously unappreciated function for DCs in direct clearance of infected cells 68 …”
Section: Spleenmentioning
confidence: 99%